Nondestructive Evaluation of Drilled Shaft Construction Anomalies Using Full Waveform Tomography of Simulated Crosshole Measurements - Kordjazi, Alireza; Coe, Joseph T.; Afanasiev, Michael (Journal of nondestructive evaluation, 2021)
Construction of drilled shafts for transportation infrastructure presents quality assurance challenges related to structural anomalies, including voids and degraded concrete. Efforts to evaluate anomalies often use stress-wave non-destructive testing (NDT) techniques such as the crosshole sonic logging (CSL) method. CSL relies on the propagation of stress waves between access tubes inserted alongside the reinforcement cage. Differences in travel time and amplitudes can be used to estimate concrete quality within the source-receiver ray paths. Crosshole tomography (CT) advances this approach further and models ray paths to solve an inverse problem based on first arrival times. However, both stress-wave methods cannot typically evaluate anomalies smaller than 10% to 15% of the shaft cross sectional area. Recent advances in wave propagation modeling have led to the development of full waveform inversion (FWI) approaches. FWI attempts to generate a more detailed tomographic model that matches the entire waveform recordings. This paper presents findings from a numerical study where full waveform tomography was performed on a portion of a drilled shaft with a structural anomaly. Crosshole stress-wave propagation was simulated using a spectral element method (SEM) forward modeler. The resulting waveforms were then used as inputs into a CT travel-time inversion algorithm using ray-path modeling and into a FWI algorithm using the entire recorded signals. The results highlighted that FWI estimated concrete velocities and the geometry of the anomaly more accurately than CT in the idealized numerical model. This was the case even though information from more sources and receiver pairs was used for the CT inversion.